HUBUNGAN PERSEPSI ORANG TUA TENTANG DAMPAK SMARTPHONE TERHADAP PERKEMBANGAN SOSIAL PADA ANAK DI KELOMPOK BERMAIN GUGUS I KECAMATAN NANGGALO KOTA PADANG - Annisa, Annisa; Marlina, Serli; Zulminiati, Zulminiati (Jurnal Ilmiah Potensia, 2019)
This study aims to determine the relationship between parents' perceptions of the impact of smartphone on social development in children in the Cluster I Group of Kecamatan Nanggalo. Parents today are mostly negligent towards their child's growth and development and rarely stimulate their children with social developmental issues and physical energy depletion and stimulating thinking and working together are no longer attractive. Freedom and freedom to play children have been seized by smartphones. This research includes a type of correlation research with quantitative methods with a total population of 30 people found in Cluster 1 in Kecamatan Nanggalo. The sampling technique is saturated sampling. The instrument used is a questionnaire. The results showed that the significance of 0,000> 0,05 and the coefficient of determination of the relationship of independent variables (parents' perception of the impact of smartphones) on the dependent variable (social development in children) was 55.3%. It can be concluded that parents' perception of the impact of smartphones has a relationship to social development in children.